Evaluation of the microbiological quality of the leaves of Solanum macrocarpum L. cultivated with the chicken’s droppings and water of marsh in Cotonou (Republic of Benin) - DOUGNON, T. VICTORIEN; BANKOLE, HONORÉ SOUROU; DOUGNON, TOSSOU JACQUES (My University, 2012)
This study has evaluated the microbiological quality of the leaves of Solanum macrocarpum L. cultivated with chicken’s droppings and water of watering. A pilot site at Glo and market-gardening sites of Houeyiho, Fidjrosse and Agongbomey were used as sites of study. The salmonellas and fecal coliforms whose Escherichia coli were required in the environment of culture of Solanum macrocarpum L. Eight samples resulting respectively from water of watering; soils and leaves were analyzed. No salmonella was detected on these samples. Water of watering of the pilot site of Glo is not contaminated by Escherichia coli compared to those of the sites of Houeyiho (1.8.104 ± 28.42 UFC/100 ml) ; Fidjrosse (0.95.104 ±70.10 UFC/100 ml) ; Agongbomey (5545 ± 77.53 UFC/100 ml) (p<0.05). The leaves of Solanum macrocarpum L. were contaminated by Escherichia coli with different degrees according to the site: Glo (35.65.104 ± 457.08 UFC/g); Houeyiho (0,95.103 ± 70.71 UFC/g); Fidjrosse (1.103 ± 0 UFC/g) ; Agongbomey (0.9.103 ± 0 UFC/g) (p<0.05). In addition, Escherichia coli have strongly developed on the leaves of Solanum macrocarpum L. from the pilot site of Glo with a neutral pH (7.305 ± 0.064) compared to the other sites: 6.550 at Houeyiho; 6.480 at Fidjrosse and 6.445 at Agongbomey (p<0.05). The study has shown that the leaves of Solanum macrocarpum L. are contaminated by the enterobacteria and their consumption may expose the populations to some risks of enteric diseases.
Keywords: Escherichia coli; salmonellas; coliforms; microbiology.